Change and the individual: expectations and triggers - Parkinson, Ann (Henry Stewart Talks, 2011)
Change and the individual: outline, Individual differences, Personality and change, Psychological contract, Psychological contract types, Four stages of psychological contracting, Role of HR practices, The employment relationship: a map of the psychological contract, Shocks and triggers, Trigger event types, Change triggers in action, Rebalancing the psychological contract, Role of the line manager, Implications for managing change, Conclusions, References